A Case-control Study of Risk Sources for Severe Fever with Thrombocytopenia Syndrome in Hubei Province, China. (February 2017) - Xing, Xuesen; Guan, Xuhua; Liu, Li; Xu, Junqiang; Li, Guoming; Zhan, Jianbo; Liu, Gongping; Jiang, Xiaoqing; Shen, Xingfu; Jiang, Yongzhong; Wu, Yang; Zhang, Hao; et al.
Abstract: Background: Severe fever with thrombocytopenia syndrome (SFTS), an emerging infectious disease caused by a novel bunyavirus, was discovered in rural areas of Central China in 2009. Methods: A case-control study based on hospital data was applied to detect the potential risk sources for SFTS in SFTS-endemic counties in Hubei Province. Cases were defined as hospitalized SFTSV confirmed patients. Controls were randomly selected from non-SFTSV patients in the same hospital ward within 2 weeks of inclusion of the cases, and they were matched by age (+/− 5 years) and gender according to 1:2 matching condition. Results: 68 cases and 136 controls participated in this study. In multivariate analysis, "Contact with cattle tick" was the major risk source (Conditional Logistic Regression OR-MH = 8.62, 95% CI = 1.79-41.51), outdoor activities and working in weeds or hillside fields could increase risk of cattle tick contact and SFTS infection (Conditional Logistic Regression OR-MH = 8.82, 95% CI = 1.69-46.05, P value = 0.01). Conclusion: Our results suggested cattle might be dominant hosts in SFTS-endemic regions in Hubei Province, which provided clues to transmission mechanism of "vectors, host animals, and humans", thus more effectively preventing and controlling the disease.